A Preliminary Study of Peer Assessment Feedback within Team Software Development Projects - Tom Crick (Proceedings of the 53rd ACM Technical Symposium on Computer Science Education V. 2, 2022)
Team-based software development projects where teams of learners design and develop software artefacts are common in computing- related degree programmes in the UK and other jurisdictions. Peer assessment is a commonly used approach to ensure learners are fairly recognised and rewarded for their contributions to such projects. This poster presents a preliminary study analysing the relationship between peer marking using the Team-Q rubric and peer feedback from one cohort using open coding and sentiment analysis. The preliminary results from a UK institutional study (N=124) illustrate how learner behaviours within teams appear to impact upon peer scores and the sentiment and intensity of emotion expressed in peer feedback. Additionally, the results provide valuable insights into common behaviours within teams. Given the prominence of team projects in computing curricula, the insights offered from this UK institutional study can shape and inform future learning, teaching and assessment practice.